The Role of Plasma Neurofilament Light Protein for Assessing Cognitive Impairment in Patients With End-Stage Renal Disease - Hou, Yi-Chou; Huang, Chuen-Lin; Lu, Chien-Lin; Zheng, Cai-Mei; Lin, Yuh-Feng; Lu, Kuo-Cheng; Chung, Ya-Lin; Chen, Ruei-Ming (Frontiers in Aging Neuroscience, 2021)
End-stage renal disease (ESRD) is defined as the irreversible loss of renal function, necessitating renal replacement therapy. Patients with ESRD tend to have more risk factors for cognitive impairment than the general population. Blood-based assays for detecting pathologic protein, such as amyloid beta (Aβ), total tau protein, and neurofilament light chain (NfL), have the advantages of being less invasive for diagnosing patients with cognitive impairment. The aim of the study is to validate if the common neurologic biomarkers differ in ESRD patients and if the specific biomarkers could correlate with correctable risk factors. Methods: In total, 67 participants aged >45 years were enrolled. The definition of ESRD was receiving maintenance hemodialysis for >3 months. Cognitive impairment was defined as a Mini-Mental State Examination score of <24. The participants were divided into groups for ESRD with and without cognitive impairment. The blood-based biomarkers (tau protein, Aβ1/40, Aβ1/42, and NfL) were analyzed through immunomagnetic reduction assay. Summary of results: The study enrolled 43 patients with ESRD who did not have cognitive impairment and 24 patients with ESRD who had cognitive impairment (Mini-Mental State Examination [MMSE]: 27.60 ± 1.80 vs 16.84 ± 6.40, p < 0.05). Among the blood-based biomarkers, NfL was marginally higher in the ESRD with cognitive impairment group than in the ESRD without cognitive impairment group (10.41 ± 3.26 vs 8.74 ± 2.81 pg/mL, p = 0.037). The concentrations of tau protein, amyloid β 1/42, and amyloid β 1/40 (p = 0.504, 0.393, and 0.952, respectively) were similar between the two groups. The area under the curve of NfL to distinguish cognitively impaired and unimpaired ESRD patients was 0.687 (95% confidence interval: 0.548–0.825, p = 0.034). There was no correlation between the concentration of NfL and MMSE among total population (r=-0.153, p=0.277), patients with (r=0.137, p=0.583) or without cognitive impairment (r=0.155, p=0.333). Conclusions: Patients with ESRD who had cognitive impairment had marginally higher plasma NfL concentrations. NfL concentration was not correlated with the biochemical parameters, total MMSE among total population or individual groups with or without cognitive impairment. The concentrations of Aβ1/40, Aβ1/42, and tau were similar between the groups.